Establishment of design streamflow hydrograph in the Rompin River Basin - Nuraini, Mahali (2019)
The Rompin River Basin one of the district area in Malaysia that often affected by flood. There are two types of floods occur in the River Basin namely the monsoon flood and flash flood. Since flood problems imposed high impact on the social economy and wellbeing such as casualties and properties damaged. It is important to understand the hydrological processes involved river basin to subsequently mitigate the flood issues. The purpose of this study are to simulate, calibrate and validate the hydrographical module and develop the IDF Curve and design rainfall for the Rompin River Basin. Hydrological model in this study was the HEC-HMS model. Hydrological data collected for 6 rainfall stations and 2 streamflow stations from 1990 to 2013 were used as the input data for verification and prediction processes. Designed rainfall patterns for the selected stations were determined for the Average Recurrence Interval (ARI) of 2 years, 5 years, 10 years, 50 years and 100 years based on the developed Intensity-Duration Frequency (IDF) Curves. For the hydrological modelling, Clark Unit hydrograph was selected as the rainfall runoff transformation method for this study in which the parameters Tc and R were estimated according to the Hydrology Procedure 27 developed by the Department of Irrigation and Drainage (DID) Malaysia. The SCS Curve Number is used as the surface roughness, while for the baseflow and lag routing, constant monthly is used. Through this study, the results show that the HEC-HMS model can sufficiently simulate streamflow hydrograph for Rompin River Basin during high flow season. Prediction of future streamflow patterns for the entire basin were developed based on the designated ARI. The outcome of this study are important to serve as decision-making supporting tool for the design of flood mitigation. Besides, it can also provide water volume for a certain rainfall event which is essential for the operational and management in Rompin River Basin water supply and flood control.